Application DFA And AHP In Design Evaluation Process For Environmental Performance In The Conceptual Design Stage A Case Study - Hasan, Muhammad Syahid (2015)
This thesis basically discusses on the application of design for assembly (DFA) method and multi criteria decision making (MCDM) tool namely analytic hierarchy process (AHP). The main objective of this study is to apply both DFA and AHP in conceptual design stage to evaluate the environmental performance of a product. Conceptual design stage is a stage where no final decision has yet been made, therefore giving more flexibility to designer to focus on environmental aspect in their design. This study was conducted by using mechanical pencil design as case study. 5 conceptual designs were developed and 3 type analysis based on Lucas DFA method were done to evaluate the design functional efficiency, feeding ratio, and fitting ratio. 10 selection criteria for AHP were considered based on literature studies which are recyclable material, renewable material, number of parts, durability, modularity, ease of maintenance, ease of disassembly, functional efficiency, feeding ratio, and fitting ratio. Through the literature study, judgements through pairwise comparison were done to the selection criteria with respect to the goal. This is to select the optimum design that has the highest environmental performance. Functional efficiency has the highest priority vector as much as 33.4% while the least important criteria is shared by feeding ratio and fitting ratio with priority vector of 1.97%. At the final stage of AHP, each alternative were sorted based on their priority vector. Conceptual design 5 was ranked 1st with priority vector of 30.41%, followed by conceptual design 2 with priority vector of 21.2%. Conceptual design 4 and conceptual design 1 followed on 3rd and 4th in ranking with priority vector of 19.49% and 15% respectively. The least preferred alternative is conceptual design 3 with priority vector of 14.02%. Then, several sets of sensitivity analysis were carried out by using Expert Choice software to study whether any changes on the selection criteria’s priority vector will affect the conceptual design ranking that were obtained on previous AHP analysis.